PENERIMAAN KONSUMEN TERHADAP BOLU KUKUS DENGAN PENAMBAHAN KENTOS KELAPA - Saputri, Heni Indra; Yulianti; Ninsix, Retti; Mardesci, Hermiza (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2025)
Indonesia is one of the largest coconut producers in the world. Coconut trees are found in almost every province across the country. Coconut apple (kentos) is a by-product commonly found in almost all areas of Indragiri Hilir Regency, where the majority of the population works as coconut farmers. The aim of this study is to transform coconut apple waste into a valuable food product that is appealing to all segments of society. The results of the study show that the steamed sponge cake with the addition of coconut apple was well accepted by the panelists based on organoleptic characteristics, including color, aroma, texture, and taste. Based on the organoleptic evaluation (color, aroma, texture, and taste), it was concluded that steamed sponge cake with added coconut apple was acceptable and preferred by the panelists. The best treatment was treatment D, which used 15% coconut apple, with organoleptic scores of 4.00 for color, 4.10 for aroma, 4.55 for texture, and 4.45 for taste.